Taʼthīr Istikhdām Wasīlah Prezi fī Ta'līm Mahārah al-Qirāʼah lada al-Ṭullāb fī al-Madrasah al-Mutawassiṭah al-Islāmīyyah al-Ḥukūmīyyah - Septiana, Nur Aini; Dewi S, Yelfi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
The study was inspired by pupils' poor reading performance, which was linked to a lack of enthusiasm in reading and a shortage of technology-based instructional resources employed by teachers. This study looks at how utilizing Prezi affects the reading ability of eighth-grade pupils at MTsN 3 Lima Puluh Kota. A true experimental design with a pretest-posttest control group was used. Analyze the data using statistical analysis by the Minitab program. In this research, the researcher uses a simple random sample. The sample of this research is the two grades, namely the Eighth Grade (6) with 28 students, and the Eighth Grade (10) with 22 students. Eighth Grade (6) as the experimental class and Eighth Grade (10) as the officer class. And the data analysis in this research is quantitative. The method of data analysis used in this research is statistical analysis with the type of semantic statistics. The data were examined with Minitab software. The hypothesis testing yielded a p-value of 0.002, showing statistical significance (p < 0.05) and an effect size of around 24.05%. The results show that using Prezi greatly enhances kids' reading ability. استُلهمت هذه الدراسة من ضعف أداء التلاميذ في مهارة القراءة، والذي ارتبط بانخفاض الحماس نحو القراءة ونقص الموارد التعليمية القائمة على التكنولوجيا التي يستخدمها المعلمون. هدفت هذه الدراسة إلى استكشاف أثر استخدام برنامج بريزي على قدرة القراءة لدى تلاميذ الصف الثامن في المدرسة المتوسطة الإسلامية الحكومية الثالثة بـليما بولو كوتا. وقد استُخدم في هذه الدراسة تصميم تجريبي حقيقي مع مجموعة ضابطة باختبار قبلي وبعدي. تم تحليل البيانات باستخدام التحليل الإحصائي من خلال برنامج مينيتاب. استخدمت الباحثة في هذه الدراسة أسلوب العينة العشوائية البسيطة. تكوّنت عينة البحث من صفين، هما الصف الثامن (6) ويضم 28 تلميذًا، والصف الثامن (10) ويضم 22 تلميذًا، حيث اعتُبر الصف الثامن (6) صفًا تجريبيًا، بينما اعتُبر الصف الثامن (10) صفًا ضابطًا. إن تحليل البيانات في هذا البحث ذو طابع كمي، وقد استُخدم فيه التحليل الإحصائي من نوع الإحصاء الدلالي. تم فحص البيانات بواسطة برنامج «مينيتاب»، وأظهرت نتائج اختبار الفرضية قيمة احتمالية (p) بلغت 0.002، مما يشير إلى وجود دلالة إحصائية عند مستوى(p < 0.05) ، بحجم تأثير يُقدّر بحوالي 24.05%. وتدل النتائج على أن استخدام برنامج بريزي يُسهم بشكل كبير في تحسين قدرة التلاميذ على القراءة.